1984
DOI: 10.1159/000238297
|View full text |Cite
|
Sign up to set email alerts
|

Intraphagocytic Bactericidal Activity of Bacterial DNA Gyrase Inhibitors against <i>Serratia marcescens</i>

Abstract: Addition of phenylbutazone (2 mg/ml) to 55 vol% of fresh defibrinated human blood permitted leukocytic ingestion of Serratia marcescens bacteria, but blocked phagocytic killing activity. The group A (phage tail) bacteriocin bA+ 16 served to kill extraphagocytic test bacteria. Five bacterial DNA gyrase inhibitors (ciprofloxacin, enoxacin, norfloxacin, nalidixic acid and pipemidic acid) revealed intraphagocytic bactericidal activity against ingested S. marcescens bacteria of three test strains; the ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
13
0

Year Published

1985
1985
1995
1995

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(14 citation statements)
references
References 7 publications
(12 reference statements)
1
13
0
Order By: Relevance
“…Although not all antimicrobial agents entering phagocytes will have therapeutic potential, quinolones have been shown to remain active intracellularly against a variety of microorganisms (3,9,12). The fluorometric assay to measure intracellular concentrations of fluoroquinolones is less laborious and more specific than the bioassay, is more sensitive than the HPLC assay, and does not require radiolabeled antimicrobial agents.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Although not all antimicrobial agents entering phagocytes will have therapeutic potential, quinolones have been shown to remain active intracellularly against a variety of microorganisms (3,9,12). The fluorometric assay to measure intracellular concentrations of fluoroquinolones is less laborious and more specific than the bioassay, is more sensitive than the HPLC assay, and does not require radiolabeled antimicrobial agents.…”
Section: Discussionmentioning
confidence: 99%
“…These antimicrobial agents are able to penetrate into phagocytes and remain active intracellularly (2,3,9,12 In this study a fluorometric assay, based on the natural fluorescence of the quinolone nucleus, was used to evaluate the uptake of ofloxacin by human polymorphonuclear leukocytes (PMN). The possible mechanism involved in the membrane transport of this antimicrobial agent is also evaluated.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Some of these effects have been observed on leukocytes. It has been found that ciprofloxacin penetrates leukocytes and reaches intracellular levels with bactericidal activity (4,20). The incorporation of [ 3 H]thymidine into T lymphocytes incubated with phytohemagglutinin was increased in the presence of fluoroquinolones, but the progression of mitogen-stimulated lymphocytes through the S and G 2 /M stages of the cell cycle and the secretion of immunoglobulins (Ig's) by pokeweed mitogen-stimulated B lymphocytes were inhibited (7).…”
mentioning
confidence: 99%
“…In the past decade, pipemidic acid (4) has been found to possess higher antibacterial activity against Pseudomonas aeruginosa, Escherichia coli, Proteus vulgaris, Klebsiella pneumoniae, and Enterobacter and Citrobacter organisms (5,(12)(13)(14) than structurally similar agents, such as piromidic (11) and nalidixic acid (3), and thus has been applied to chemotherapy of parenchymatous urinary tract infections. The known chronic and acute toxicities of pipemidic acid are rather low (6)(7)(8)(9); however, numerous pharmacokinetic studies have been conducted to determine the most effective concentrations in serum for clinical use.…”
mentioning
confidence: 99%